Carbon trading's impact on California's real-time electricity market prices. (15th September 2018) - Woo, C.K.; Chen, Y.; Zarnikau, J.; Olson, A.; Moore, J.; Ho, T.
Abstract: What is the extent of a real-time electricity market's pass-through of the marginal cost of CO2 emissions due to a cap-and-trade (C&T) program? This is an important policy question, as an incomplete pass-through would suggest the program's limited effectiveness in achieving efficient pricing of electricity. To answer the question, we perform a regression analysis of California's electricity market data for a 65-month period of 01/01/2011–05/31/2016. Based on this newly constructed large sample, we find that the California Independent System Operator's real-time market prices contain a CO2 premium that closely tracks the marginal cost of CO2 emissions of California's natural-gas-fired generation units, which are often at margin that determines the power prices. While the CO2 premium provides much needed incentives for renewable energy development, it does little to improve the incentive for natural-gas-fired generation investment in California. Hence, procurement of dispatchable generation capacity via long-term contracts continues to be useful for the state to meet the mandatory criteria for resource adequacy and system reliability. Highlights: Estimate carbon trading's impact on electricity prices in California's real-time market (RTM). Use a large sample of daily market data to show the RTM's 100% pass-through of the CO2 price. Document that the RTM prices by time-of-day period move the CO2 price and other fundamental drivers. Discuss the policy implications of the RTM's 100% pass-through of the CO2 price.